Физика мен химияның арасындағы ғылым философиясы - Müürsepp, P. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
The paper deals with the main problems of the philosophy of science from a new perspective. The analysis takes off from Rein Vihalemm’s novel approach to scientific research called practical realism. From this perspective science is not only theoretical but first and foremost a practical activity. This kind of approach puts chemistry rather than physics into the position of a typical science as chemistry has a dual character resting on both constructive-hypothetico-deductive (ϕ-science) and classifying-historico-descriptive (non-ϕ-science) types of cognition. Chemists deal with finding out the laws of nature like the physicists. However, in addition to this they deal with substances or stuff that is rather an activity typical to natural history. The analysis of the dual character of chemistry brings forward the need to analyse philosophically the reasons why physics has held the position of the only science proper so far. This can be and done from the perspective of practical realism as well. There is a brief look into the essence of biology in the paper. The conclusion is, however, that the typical science of dual character is chemistry and this philosophical discovery may change the future perspective of the whole philosophy of science. Key words: dual character of chemistry, ϕ-science, philosophy of science, physics, practical realism, Rein Vihalemm.